Membangun Kembali Komunikasi Organisasi Karang Taruna Di Desa Kedung Kampil Kecamatan Porong - Muhimmatur Rodhiyah; Wahyu Eko Pujianto (Jurnal Pengabdian Kepada Masyarakat, 2023)
This research is in-depth about the crucial role of communication in rebuilding and maintaining the solidarity of the Karang Taruna organization in Kedung Kampil Village Rw.04, Porong District, Sidoarjo Regency, after experiencing a period of hiatus from 2015 to 2019. The focus of the research is aimed at the efforts of Ahmad Syafi'udin, The chairman of Karang Taruna, in approaching village youth, forms a clear organizational structure and establishes effective communication. The success of this organization in 2019 reflects the positive impact of establishing a good structure, increasing village youth participation, and implementing various programs, including regular flights every Friday, building sports facilities, commemorating the Republic of Indonesia's Independence Day, and utilizing YouTube social media. The importance of the role of communication in maintaining solidarity is the main highlight, with this research trying to provide an understanding to Karang Taruna members about the significance of communication in developing a better organization. Analysis of communication patterns implemented by the Karang Taruna organization in Kedung Kampil Village is the focus for answering the research problem formulation. In responding to challenges, this organization adopted a revitalization strategy through efforts to increase internal and external communication, improve organizational structure, and design more measurable work programs. In addition, this research discusses the impact of the Industrial Revolution 4.0 on the global business ecosystem, with an emphasis on data technology. The structural transformation of organizations, the application of artificial intelligence, and changes in the paradigm of global business interactions are the central points. The research conclusions show that a deep understanding of these changes is the key to ensuring business sustainability and competitiveness in the era of Industrial Revolution 4.0. In recommendations, the study advises companies to invest in human resources skilled in data technology and artificial intelligence and strengthen cross-border partnerships to face challenges and exploit emerging opportunities